New perspectives on youth migration: Motives and family investment patterns - Heckert, Jessica (Max Planck Institute for Demographic Research, 2015)
Migration research commonly assumes that youth migrate as dependent family members or are motivated by current labor opportunities and immediate financial returns. These perspectives ignore how migration experiences, specifically motives and remittance beh